2019
DOI: 10.1088/2053-1583/ab33ae
|View full text |Cite
|
Sign up to set email alerts
|

Multi-wafer batch synthesis of graphene on Cu films by quasi-static flow chemical vapor deposition

Abstract: The chemical vapor deposition (CVD) of graphene on thin Cu film wafers is highly desirable for the development of technological applications as it offers superior flatness, rigidity, high purity, and compatibility with conventional thin film techniques. Here, we report the high-throughput synthesis of uniform single-layer highly crystalline graphene on a batch of 3-inch wafers. The production throughput is optimized by using closely-packed vertically-standing wafers instead of placing them flat on a horizontal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…First, confined configurations are effective for building quasistatic conditions. [ 34,56 ] Ultimately, growth carboneous intermediates reside for longer periods around the growth surface, which increase the chances of growth. Second, such setups control/reduce growth bearing moieties flow reaching the substrate deposition face, guaranteeing nucleation density suppression.…”
Section: Future Perspectivementioning
confidence: 99%
See 3 more Smart Citations
“…First, confined configurations are effective for building quasistatic conditions. [ 34,56 ] Ultimately, growth carboneous intermediates reside for longer periods around the growth surface, which increase the chances of growth. Second, such setups control/reduce growth bearing moieties flow reaching the substrate deposition face, guaranteeing nucleation density suppression.…”
Section: Future Perspectivementioning
confidence: 99%
“…In view of this, future research is required to achieve precise control on the frequency and location of nucleation number on the fabrication surfaces, and more importantly, to encourage confined approach intervened industrial scale fabrication, as shown in Figure 12e and references. [ 12,56 ] To overcome these limitations, a more detailed future study is vital, and the real‐time and in situ observations can help researchers gain a closer look at the changes inside the reaction chamber during graphene growth. Therefore, the collected information could be used to improve the existing graphene growth mechanism.…”
Section: Future Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…Hu et al reported the relationship between gas flow rate and graphene structure quality and deposition uniformity [ 171 ]. The gas flow rate in the CVD furnace under different Cu substrate structures is simulated by CFD.…”
Section: Simulation Of Synthesis Process Of Carbon Materials Prepared By Cvdmentioning
confidence: 99%